The Antibacterial Activity Test Of Leaf Extract Nanoparticles Of Senggani (Melastoma Candidum D.Don) Against Cutibacterium Acnes And Staphylococcus Epidermidis Bacteria - Tia Nazilla; Muhammad Amin Nasution; Minda Sari Lubis; Rafita Yuniarti (Jurnal EduHealth, 2024)
The aim of this research is to explore and delve deeper into the reasons families request passive euthanasia, the illnesses and conditions that lead individuals to consider such actions, and how the principle of patient autonomy is applied in euthanasia practices at KH. Daud Arif Regional General Hospital, Kuala Tungkal. The research employs a qualitative approach through literature review studies. Data were collected from journals, books, and previous studies, focusing on the withdrawal of life-support measures and the ethical principle of autonomy. The collected information was analyzed to support the research. Based on the findings, decisions regarding euthanasia, particularly passive euthanasia, should ideally be made by patients when they are mentally capable. However, in critical conditions where the patient is incapacitated, the responsibility is transferred to the patient's family, who can make decisions on their behalf, including opting for passive euthanasia. While active euthanasia remains illegal in Indonesia, passive euthanasia, such as the cessation of life-support interventions, is permitted under certain legal frameworks, such as Ministry of Health Regulation No. 37 of 2014. This regulation also emphasizes the importance of therapeutic contracts between patients and healthcare providers. The reasons families or patients choose passive euthanasia at KH. Daud Arif Regional General Hospital, Kuala Tungkal, include prolonged physical suffering and a significant decline in quality of life. The illnesses or conditions considered for passive euthanasia include chronic, incurable diseases that cause ongoing suffering, such as heart disease, kidney failure, or illnesses with poor prognoses.